Зміст діяльності прокуратури як суб’єкта оперативно-розшукового запобігання злочинам - Новосад, Ю.; Novosad, Yu. (Східноєвропейський національний університет імені Лесі Українки, 2016)
В статті розглянуті проблемні питання, що стосуються роботи органів прокуратури у сфері оперативно-розшукової діяльності як суб’єктів запобігання злочинам, визначені дискусійні та недостатньо врегульовані нормами права моменти а також запропоновані науково обґрунтовані шляхи їх вирішення по суті. Ensuring legal order, respect for human rights andfreedoms are the priorities of today's policy of Ukraine on the way to integration into the European community. Today, in the conditions of legal reform in Ukraine, as well as asignificant increase in crime rates in recent years (2014-2016), the issues of enhancing the level of efficiency and the role of the prosecutor's office in the system of subjects fighting the crimes have become extremely important. The article describes the activities of the prosecutor's office through the prism of realization of content elements of operational-investigative measures of crime prevention. The author pays special attention to the study of such legal phenomenon as «operativesearch prevention», which is one of the priorities of counteraction to criminality. It implies operationalinvestigative prevention of crime, detection of latent crimes and those who committed them, as well as the operative-search counteraction to obstruction of criminal proceedings. Having determined the debatableand insufficiently regulated by the rule of law issues,that concern precisely the content of the activities of the prosecutor's office as a subject of operative-investigative crime prevention, the author offers scientifically substantiated ways of solving them essentially.
Content of the Public Prosecutor's Office Activity as the Subject of OperationalInvestigative Prevention of Crime.
Keywords: оперативно-розшукова діяльність; суб’єкт; запобігання; прокуратура; злочин; функції; завдання; орган; механізм; держава; operational-investigative activity; subject; prevention; the prosecutor's office; a crime; function; The task; organ; mechanism; state